Evaluation of Distance Learning in Pre-schools During the New Pandemic Era - Salwiah; Yuliani M, Sri; Asmuddin; Nur Hidayah, Afifah; Irawaty (Jurnal Pendidikan Usia Dini, 2022)
Distance learning at the pre-school level requires evaluation action considering that this form of learning is a new process for most elements of education in early childhood education. The purpose of this study is to evaluate virtual learning, namely planning, implementation, and assessment, as well as revealing the obstacles that occur in online learning in Kendari City Kindergarten. This study uses descriptive quantitative research methods with data collection techniques through surveys. The results showed that planning for online learning had been carried out by coordinating between teachers and parents, as well as drafting a learning plan from home starting from standard learning operations, semester programs, weekly and daily lesson plans. The implementation of learning uses several facilities, including WhatsApp application (62.50%), Zoom meeting application (12.50%), learning videos (12.50%), Google Meet (6.25%), and YouTube (6.25%). Children's learning methods currently include giving assignments (32.26%), performance (25.81%), demonstrations (22.58%) and experiments (19.35%). While the media used are video, picture media and children's worksheets. The assessment used by the teacher is in the form of portfolio assessment (50%), performance (30%) and observation (20%). The obstacles faced by teachers during distance learning are the lack of cooperation from parents when accompanying children to study at home, parents who are often late in collecting their children's assignments (portfolios), and the lack of smart phone facilities owned by parents. In response to this, good communication and collaboration between teachers and parents are needed, and parents must be able to pay attention and motivate children during the distance learning process, especially in the new pandemic era. Keywords: pre-school, distance learning, ECE evaluationReferences: Ariswari, N. K. R., & Tirtayani, L. A. (2021). Survei Kesiapan Orang Tua dalam Mendampingi Proses Pembelajaran Anak Usia Dini Berbasis Daring [Survey on Parental Readiness in Assisting the Online-Based Early Childhood Learning Process]. 5(1), 10. Atiles, J. T., Almodóvar, M., Chavarría Vargas, A., Dias, M. J. A., & Zúñiga León, I. M. (2021). International responses to COVID-19: Challenges faced by early childhood professionals. European Early Childhood Education Research Journal, 29(1), 66–78. https://doi.org/10.1080/1350293X.2021.1872674 Bassok, D., Michie, M., Cubides-Mateus, D. M., Doromal, J. B., & Kiscaden, S. (2020). The Divergent Experiences of Early Educators in Schools and Child Care Centers during COVID-19: Findings from Virginia. 28. Beckerman, M., van Berkel, S. R., Mesman, J., & Alink, L. R. A. (2017). The role of negative parental attributions in the associations between daily stressors, maltreatment history, and harsh and abusive discipline. Child Abuse & Neglect, 64, 109–116. https://doi.org/10.1016/j.chiabu.2016.12.015 Bigras, N., Lemay, L., Lehrer, J., Charron, A., Duval, S., Robert-Mazaye, C., & Laurin, et I. (2021). Early Childhood Educators’ Perceptions of Their Emotional State, Relationships with Parents, Challenges, and Opportunities During the Early Stage of the Pandemic. Early Childhood Education Journal, 49(5), 775–787. https://doi.org/10.1007/s10643-021-01224-y Bilbokaitė-Skiauterienė, I., & Bilbokaitė, R. (2021). Opportunities of Organizing and Implementing Distance Learning: The Context of Lithuanian Pre-School Teachers’ Opinions. 10115–10122. https://doi.org/10.21125/edulearn.2021.2085 Brown, S. M., Doom, J. R., Lechuga-Peña, S., Watamura, S. E., & Koppels, T. (2020). Stress and parenting during the global COVID-19 pandemic. Child Abuse & Neglect, 110, 104699. https://doi.org/10.1016/j.chiabu.2020.104699 Creswell, J. W. (2015). Educational research: Planning, conducting, and evaluating quantitative and qualitative research (Fifth edition). Pearson. Darling-Hammond, L., Schachner, A., & Edgerton, A. K. (2020). Restarting and Reinventing School: Learning in the Time of COVID and Beyond. 126. Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review, 118, 105440. https://doi.org/10.1016/j.childyouth.2020.105440 Ford, T. G., Kwon, K.-A., & Tsotsoros, J. D. (2021). Early childhood distance learning in the U.S. during the COVID pandemic: Challenges and opportunities. Children and Youth Services Review, 131, 106297. https://doi.org/10.1016/j.childyouth.2021.106297 Guilar, J. D., & Loring, A. (2008). Dialogue and Community in Online Learning: Lessons from Royal Roads University. 22. Lau, E. Y. H., & Lee, K. (2020). Parents’ Views on Young Children’s Distance Learning and Screen Time During COVID-19 Class Suspensio. Early Education and Development, 19. https://doi.org/10.1080/10409289.2020.1843925 Ma, X., Shen, J., Krenn, H. Y., Hu, S., & Yuan, J. (2016). A Meta-Analysis of the Relationship Between Learning Outcomes and Parental Involvement During Early Childhood Education and Early Elementary Education. Educational Psychology Review, 28(4), 771–801. https://doi.org/10.1007/s10648-015-9351-1 Malta Campos, M., & Vieira, L. F. (2021). COVID-19 and early childhood in Brazil: Impacts on children’s well-being, education, and care. European Early Childhood Education Research Journal, 29(1), 125–140. https://doi.org/10.1080/1350293X.2021.1872671 Mark Nichols. (2003). A theory for eLearning. Journal of Educational Technology & Society, 6(2), 1–10. JSTOR. McKenna, M., Soto-Boykin, X., Cheng, K., Haynes, E., Osorio, A., & Altshuler, J. (2021). Initial Development of a National Survey on Remote Learning in Early Childhood During COVID-19: Establishing Content Validity and Reporting Successes and Barriers. Early Childhood Education Journal, 49(5), 815–827. https://doi.org/10.1007/s10643-021-01216-y Prime, H., Wade, M., & Browne, D. T. (2020). Risk and resilience in family well-being during the COVID-19 pandemic. American Psychologist, 75(5), 631–643. https://doi.org/10.1037/amp0000660 Reich, J., Buttimer, C. J., Fang, A., Hillaire, G., Hirsch, K., Larke, L. R., Littenberg-Tobias, J., Moussapour, R. M., Napier, A., Thompson, M., & Slama, R. (2020). Remote Learning Guidance from State Education Agencies During the COVID-19 Pandemic: A First Look [Preprint]. EdArXiv. https://doi.org/10.35542/osf.io/437e2 Russell, B. S., Hutchison, M., Tambling, R., Tomkunas, A. J., & Horton, A. L. (2020). Initial Challenges of Caregiving During COVID-19: Caregiver Burden, Mental Health, and the Parent–Child Relationship. Child Psychiatry & Human Development, 51(5), 671–682. https://doi.org/10.1007/s10578-020-01037-x Safi, F., Wenzel, T., & Spalding, L.-A. T. (2020). Remote Learning Community: Supporting Teacher Educators During Unprecedented Times. Journal of Technology and Teacher Education, 28(2), 211–222. Spinelli, M., Lionetti, F., Pastore, M., & Fasolo, M. (2020). Parents’ Stress and Children’s Psychological Problems in Families Facing the COVID-19 Outbreak in Italy. Frontiers in Psychology, 11, 1713. https://doi.org/10.3389/fpsyg.2020.01713 Szente, J. (2020). Live Virtual Sessions with Toddlers and Preschoolers Amid COVID-19: Implications for Early Childhood Teacher Education. Journal of Technology and Teacher Education, 28(2), 373–380. Tao, S. S., Lau, E. Y. H., & Yiu, H. M. (2019). Parental Involvement After the Transition to School: Are Parents’ Expectations Matched by Experience? Journal of Research in Childhood Education, 33(4), 637–653. https://doi.org/10.1080/02568543.2019.1653409